The Three Rs: Resolving Respiration Robotically in Shelf Seas. Issue 4 (22nd February 2022) - Williams, C. A. J.; Davis, C. E.; Palmer, M. R.; Sharples, J.; Mahaffey, C.
Abstract: Ocean deoxygenation threatens ocean productivity, carbon cycling and marine ecosystems. Shelf seas are highly dynamic regions, which contributes to their high productivity and also makes monitoring and constraining their oxygen status a challenge. Here, using the temperate Celtic shelf sea (April and July 2015) as a case study, we present high‐resolution ocean glider observations of turbulence and biogeochemical parameters, demonstrating the potential of these autonomous platforms for environmental monitoring. We estimate vertical turbulent oxygen fluxes be 25% higher in summer than in spring, due to the presence of subsurface chlorophyll and associated oxygen maxima at the seasonal thermocline. We demonstrate that glider‐based estimates were able to constrain similar bottom layer respiration rates as those derived from traditional ship‐based measurements. We suggest ocean gliders are useful monitoring tools that can aid sustainable management of shelf sea ecosystems. Plain Language Summary: Oxygen levels in the ocean are decreasing. Oxygen is needed by almost all life in the oceans, thus low oxygen levels can result in dramatic changes to marine ecosystems. The decrease in oxygen levels is particularly alarming in the coastal ocean or "shelf sea" (the region between the land and the deep open ocean), which supports the majority of global fisheries (over 90%). Therefore, there is both an urgent societal and an environmental need to better understand processes influencing oxygen levels in the coastal ocean, such as physical water circulation and mixing, and biological oxygen production and consumption. Here we present turbulent mixing data collected over 40 days in a typical shelf sea using an unmanned, autonomous underwater vehicle (AUV) called an ocean glider. We use this data combined with oxygen data to calculate the contribution of physical oxygen fluxes to the observed change in oxygen, and from this deduce how much of the change was driven by biology. We prove that AUVs may be used as an effective method for monitoring oxygen dynamics and that this can aid responsible marine management in shelf seas. Key Points: Glider observations are able to integrate physical and biogeochemical processes influencing oxygen depletion in shelf seas Mixing and advection replenish respired oxygen in the bottom mixed layer The presence of a subsurface oxygen maxima results in larger oxygen fluxes to the bottom mixed layer in summer compared to spring